Relación entre maduración, sexo y nivel socio-económico a través del Test Guestaltico Visomotor de Bender - Ráez de Ramírez, Matilde (1986)
The present study explores the relation between age, sex and socio-economical level in 1,019 children from 5 years to 1 O years, 11 months with the Bender Gestalt Test, using the Kippitz Developmental Scoring System. No significant differences were found according to sex or socio-economical level. Comparing the results with those of Koppitz, significant differences were found in 8 of the 12 groups studied. It was also found that the test is only developmental untill 9 years, just as Taylor & als. results.